2018
DOI: 10.3168/jds.2017-13824
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary vitamin D3 and 25-hydroxyvitamin D3 supplementation on plasma and milk 25-hydroxyvitamin D3 concentration in dairy cows

Abstract: Milk enriched with vitamin D by supplementing dairy cow diets could provide a valuable dietary source of vitamin D, but information on the feasibility of this approach is limited. In the current study, the effects of supplementing dairy cows with either vitamin D or 25(OH)D over the transition/early lactation period on plasma and milk vitamin D concentrations were compared. Sixty dairy cows were randomly allocated to 1 of 4 dietary treatments from 14 d precalving to 56 d postcalving. Treatments were a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
(48 reference statements)
1
11
0
2
Order By: Relevance
“…However, although a statistically significant increase in vitamin D3 and 25(OH) D3 has been reported after biofortification at supplemental quantities in line with EU legislation (2), these changes are quantitatively trivial and would not contribute to increase in dietary vitamin D3 intake and human vitamin D status as stated by Drs Hill and Kryiazakis (1). We confirmed this in a recent study (3) in which dairy cows' diets were supplemented either with 0.075mg/kg vitamin D3 (control), the maximum permitted dose of vitamin D3 (0.1mg/kg) recommended by the EU (2), or with 0.03mg/kg vitamin D3 plus 25(OH) D3 (0.075 mg/kg) for 8 weeks feeding from calving to early lactation. The vitamin D3 and 25(OH) D3 concentrations in milk from both treatments were not significantly different to the control milk or to themselves (3).…”
supporting
confidence: 78%
“…However, although a statistically significant increase in vitamin D3 and 25(OH) D3 has been reported after biofortification at supplemental quantities in line with EU legislation (2), these changes are quantitatively trivial and would not contribute to increase in dietary vitamin D3 intake and human vitamin D status as stated by Drs Hill and Kryiazakis (1). We confirmed this in a recent study (3) in which dairy cows' diets were supplemented either with 0.075mg/kg vitamin D3 (control), the maximum permitted dose of vitamin D3 (0.1mg/kg) recommended by the EU (2), or with 0.03mg/kg vitamin D3 plus 25(OH) D3 (0.075 mg/kg) for 8 weeks feeding from calving to early lactation. The vitamin D3 and 25(OH) D3 concentrations in milk from both treatments were not significantly different to the control milk or to themselves (3).…”
supporting
confidence: 78%
“…No reference range exists for 3-epi-25(OH)D3 in humans, therefore data from a systemic review which reported ranges from several studies was used (see Bailey et al (2013) [79]). The number of studies included to provide data for each of the veterinary species are as follows: (A) dogs n = 8 [80][81][82][83][84][85][86][87], cats n = 1 [85], horses n = 1 [88], sheep n = 4 [30,[89][90][91], cattle n = 2 [92,93], pigs n = 1 [94], poultry n = 2 [95,96] and nonhuman primates n = 2 [97,98]; (B) dogs n = 2 [81,85] and cats n = 1 [85]; and C. dogs n = 1 [83]. nd = no data available for the metabolites measured by LC-MS/MS in that species.…”
Section: Comparative Differences In Vitamin D Metabolismmentioning
confidence: 99%
“…As such, studies investigating the most efficient way to supplement cattle with vitamin D have been conducted, comparing whether vitamin D or 25(OH)D supplementation is most effective. Supplementation with 25(OH)D3 over vitamin D3 has been demonstrated to improve plasma concentrations of 25(OH)D more effectively [92,93]; there was no difference between the two metabolites ability to improve milk 25(OH)D concentrations [93] but 25(OH)D supplementation increased 25(OH)D3 levels in tissues greater than supplementation with vitamin D3 [92]. Weir et al (2017) have reviewed environmental and genetic factors that influence the vitamin D content of cow's milk [145].…”
Section: Cattlementioning
confidence: 99%
“…Our recent milk biofortification study (Guo et al . ) used a total of 60 dairy cows randomised to vitamin D 3 or 25(OH)D 3 dietary supplementing treatments, within the maximum permitted European Union (EU) vitamin D 3 concentration (2 mg/day vitamin D 3 ) for feed. The results showed that supplementing dairy cows’ feed with 25(OH)D 3 significantly increased the circulating plasma concentrations of 25(OH)D 3 in the cows.…”
Section: Food Fortification With Vitamin Dmentioning
confidence: 99%